2012
DOI: 10.1351/pac-con-12-02-15
|View full text |Cite
|
Sign up to set email alerts
|

Why are the low-energy protein normal modes evolutionarily conserved?

Abstract: Proteins fluctuate, and such fluctuations are functionally important. As with any functionally relevant trait, it is interesting to study how fluctuations change during evolution. In contrast with sequence and structure, the study of the evolution of protein motions is much more recent. Yet, it has been shown that the overall fluctuation pattern is evolutionarily conserved. Moreover, the lowest-energy normal modes have been found to be the most conserved. The reasons behind such a differential conservation hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…This work laid the foundation for exploring the evolutionary conservation of dynamics in the lowest energy modes, which they further developed and validated across larger standard datasets from the family to superfamily levels [98,99]. While this work clearly confirms that low-energy normal modes are conserved between structurally conserved proteins, it is interesting to note that this conservation can be explained as the structural response to random perturbations, rather than necessarily selective pressure on certain kinds of motion [35,100,101].…”
Section: Comparing Dynamics Between More Distantly Related Proteinsmentioning
confidence: 68%
“…This work laid the foundation for exploring the evolutionary conservation of dynamics in the lowest energy modes, which they further developed and validated across larger standard datasets from the family to superfamily levels [98,99]. While this work clearly confirms that low-energy normal modes are conserved between structurally conserved proteins, it is interesting to note that this conservation can be explained as the structural response to random perturbations, rather than necessarily selective pressure on certain kinds of motion [35,100,101].…”
Section: Comparing Dynamics Between More Distantly Related Proteinsmentioning
confidence: 68%
“…The low frequency modes yield deformations at the lowest energetic cost and have been shown to be functionally relevant [62,63]. Kurkcuoglu et al showed that global motions of functional loops were important for fitting and binding of the substrate [64].…”
Section: Resultsmentioning
confidence: 99%
“…The collective motions known to support function have been shown to be well described by the lowest energy modes [63,71]. Those modes in NATs contain large movements of the β6β7 hairpin loop with hinges found at the extremities of the neighbouring strands.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the pioneering work of the Ortiz group who demonstrated that the subspaces spanned by evolutionary variation and low frequency normal modes intersect significantly, several groups studied the evolutionary variation of protein dynamics probed by ENM. Echave, after rationalizing the relationship between protein structure changes upon mutation and normal modes with a neutral model that models protein structure changes as the response of the elastic network to the perturbation induced by the mutation, found that the lowest frequency normal modes are the most conserved ones between evolutionarily related proteins, but realized that this conservation is likely evolutionarily neutral, since it cannot be distinguished from the prediction of his neutral model . Micheletti and coworkers proposed a dynamics‐based alignment of proteins by identifying regions with similar collective dynamics, as predicted by ENM .…”
Section: Applications Of Nmamentioning
confidence: 99%